Face to Face vs Virtual Teaching at the University Level (Docentes 2.0 Journal, 2023)
Due to the pandemic experienced in 2020, there was a turn in the educational field. Students had to adapt to the new educational modality through digital platforms to return to face-to-face teaching later. The objective was to know the student's opinion on which of the two face-to-face or virtual educational modalities he lived in before and during the COVID-19 pandemic was the one that generated the most academic achievement and in which activities he obtained the most benefit. The research was based on the deductive method, positivist paradigm with a quantitative approach, non-experimental design, descriptive type, and cross-section. The population surveyed was 115 students at a public university who met the requirement of having completed at least one semester in person and another online. The Cronbach's Alpha was generated for the instrument, obtaining a value of .952, which consisted of 22 items divided into three dimensions. A Likert scale with five response levels was used for the student's response options. Four data analyzes were carried out, and as a result, it was obtained that the student favors the face-to-face modality for the development of all academic activities and the feedback provided by the professor. In contrast, in virtual modality, they prefer developing the topics and applying exams. Concluding that for the student to take a learning unit in a mixed modality would be ideal, determining it by the type of activity to be carried out.
Keywords: Face to face teaching; virtual teaching; college teaching; student